Downregulation of Ezrin Suppresses Migration Potential in Cervical Cancer Cells - Marta Hałas-Wiśniewska; Wioletta Arendt; Alina Grzanka; Magdalena Izdebska (Pharmaceuticals)
Background: The literature reports that ezrin (EZR) is important as a linker between microfilaments and cellular environments. Moreover, it affects cancer cell migration, but the exact mechanism is not fully understood. In this study, we aimed to investigate the role of EZR in the migration of two different types of cervical cancer cells—from primary lesion (SiHa) and lymph node metastases (HT-3). In addition, we showed for the first time that a reduced EZR protein level affects the cellular response to the routinely used treatment with cisplatin. Methods: The most important stage of the study consisted of conducting a series of tests enabling the assessment of the migration potential of cervical cancer cells without altered EZR expression and with silenced protein expression. Results: Reducing the EZR level resulted in a decrease in the invasive and migration potential of SiHa and HT-3 cells’ inhibition of colony formation, a decrease in adhesive properties, and a strong reorganization of F-actin with a dominance of cells with a mitotic catastrophe phenotype. A lower level of protein significantly reduces the motor skills of SiHa and HT-3 cervical cancer cells. Conclusions: This significantly affects the assessment of EZR as a potential factor that can limit the development of metastases in targeted cancer therapy of cervical cancer.